Criticism of “epileptic personality” syndrome - A. Jasionis (Neurologijos seminarai)
“Epileptic personality” syndrome, sometimes known as Waxman-Geschwind syndrome, is a constellation of interictal changes of emotions, thinking and behaviour, long associated with epilepsy. We frequently accept the existence of this syndrome as self-explanatory and unquestionable, however, there is no mention of alterations of personality in the current ILAE definition of epilepsy as well as in current psychiatric diagnostic manuals (DSM-V and ICD-10). As a disturbance of personality, the syndrome is dangerously perceived as inevitable and constant. This prevents us from the possibility of symptom correction and also increases stigma perceived by people with epilepsy. The article shortly discusses the scientific evidence of “epileptic personality” syndrome and possible alternative explanations of the symptoms.